MEDICAL TOURISM AS A PROMISING DIRECTION FOR THE TOURISM INDUSTRY IN THE REPUBLIC OF KAZAKHSTAN - G.U. Khajiyeva; A.B. Irkitbayeva; A. Yerlanuly (World Scientific Reports, 2023)
One of the fastest growing areas of tourism today is medical tourism. With increasing globalisation and advances in medical technology, patients now have access to a wider range of medical care than ever before. From simple cosmetic surgery to cancer treatment, medical tourism provides patients with the opportunity to receive high quality medical care at a fraction of the price they would pay at home. Despite the increasing popularity of this area of tourism, there is no well-established scientific definition for the concept of medical tourism. According to a number of authors, medical tourism occurs when consumers decide to travel across international borders with the intention of receiving some form of medical treatment [1]. M.D. Horowitz and J.A. Rosensweig consider medical tourism as a type of tourism in which citizens from developed countries travel to less developed countries to obtain medical services, mainly due to a significant difference in price, while travelling in the opposite direction, where patients from less developed countries seek treatment in more developed countries they consider as a traditional method of treatment, and they do not include it in the medical tourism category [2]. G.Y. Shchekin defines medical tourism as medical care provision realised through tourist services [3]. The World Tourism Organization recommends the following characteristic of medical tourism: "medical tourism covers those types of tourism which have as their main motivation the contribution to physical, mental and/or spiritual health through medical and health-improving activities which increase the ability of people to satisfy their own needs and to function better as individuals in the environment and society". [4].